Hybrid zinc oxide nanocoating on titanium implants: Controlled drug release for enhanced antibacterial and osteogenic performance in infectious conditions - Zhou, Juncen; Wang, Hanbo; Virtanen, Sannakaisa; Witek, Lukasz; Dong, Hongzhou; Thanassi, David; Shen, Jie; Yang, Yunzhi Peter; Yu, Cunjiang; Zhu, Donghui (Acta Biomaterialia, 2024)
Implant-associated bacterial infections are a primary cause of complications in orthopedic implants, and localized drug delivery represents an effective mitigation strategy. Drawing inspiration from the morphology of desiccated soil, our group has developed an advanced drug-delivery system augmented onto titanium (Ti) plates. This system integrates zinc oxide (ZnO) nanorod arrays with a vancomycin drug layer along with a protective Poly(lactic-co-glycolic acid) (PLGA) coating. The binding between the ZnO nanorods and the drug results in attached drug blocks, isolated by desiccation-like cracks, which are then encapsulated by PLGA to enable sustained drug release. Additionally, the release of zinc ions and the generation of reactive oxygen species (ROS) from the ZnO nanorods enhance the antibacterial efficacy. The antibacterial properties of ZnO nanorod-drug-PLGA system have been validated through both in vitro and in vivo studies. Comprehensive investigations were conducted on the impact of bacterial infections on bone defect regeneration and the role of this drug-delivery system in the healing process. Furthermore, the local immune response was analyzed and the immunomodulatory function of the system was demonstrated. Overall, the findings underscore the superior performance of the ZnO nanorod-drug-PLGA system as an efficient and safe approach to combat implant-associated bacterial infections. Statement of significance: Implant-associated bacterial infections pose a significant clinical challenge, particularly in orthopedic procedures. To address this, we developed an innovative ZnO nanorod-drug-PLGA system for local antibiotic delivery on conventional titanium implants. This system is biodegradable and features a unique desiccation-like structure that enables sustained drug release, along with the active substances released from the ZnO nanorods. In a rat calvarial defect model challenged with S. aureus, our system demonstrated remarkable antibacterial efficacy, significantly enhanced bone defect regeneration, and exhibited local immunomodulatory effects that support both infection control and osteogenesis. These breakthrough findings highlight the substantial clinical potential of this novel drug delivery system and introduce a transformative coating strategy to enhance the functionality of traditional metallic biomaterials.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Anti-bacterial; Biodegradable coating; Controlled drug releasing; Osteogenesis; Zinc oxide nanorod